Optimization of Extraction Conditions and Kinetics of Antioxidant Compounds from Polyalthia longifolia Leaves - Clark, Poro David (Sciences of Phytochemistry, 2026)
This study aimed to optimize phenolic antioxidant extraction from Polyalthia longifolia leaves using hot maceration with 70% ethanol and to characterize the extraction kinetics under optimal conditions. Response surface methodology was used to evaluate the effects of extraction time and temperature on extraction yield, total phenolic content (TPC), and ferric reducing antioxidant power (FRAP). Both factors significantly influenced all responses, with the extraction yield and TPC increasing progressively with temperature and time. FRAP, however, exhibited a dome-shaped response, peaking at intermediate temperatures before declining under prolonged high-temperature conditions, consistent with the thermal degradation of heat-labile antioxidants. The highest phenolic recovery and antioxidant activity were achieved at the upper boundary of the experimental domain, suggesting that the true optimum may lie beyond the conditions tested. Kinetic analysis further revealed that antioxidant-active compounds were mobilized faster than the bulk extractable mass, with implications for reducing extraction time and energy consumption at scale. These findings provide a statistically guided and kinetically informed foundation for the valorization of Polyalthia longifolia leaves, supporting future process optimization across broader solvent systems and extraction techniques for functional food and nutraceutical applications.